Co to jest dokument i czy pytanie to ma jakiekolwiek znaczenie? (Na marginesie Pięciu nieczystych zagrań Larsa von Triera i Jørgena Letha) - Koschany, Rafał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article is an attempt to interpret The Five Obstructions, a film by Lars von Trier and Jørgen Leth that is a documentary record of a real meeting between the two directors, and of the project they undertook. According to plans, Leth was supposed to make five new versions of his film The Perfect Human from 1967. The result of Trier and Leth’s cooperation represents a hybrid of genres, difficult to classify by means of standard categories. Most of all, however, the film is self-referential, and therefore, the article discusses different aspects of documentary work in general, including the originality of a work of art, the issue of difference and repetition, the situation of the creator, and the concept and status of a work of art. Ultimately, the interpreted film provides a potential starting point for formulating a thesis on the documentary as a set of artistic conventions and rules for creatively engaging art and reality.